Su alcuni ritorni nella poesia polacca del secondo Novecento: l’interiorizzazione dello spazio negato (e la sua parziale riscoperta) - Alessandro Achilli (Pl.it)
In this article, I offer an overview of the return theme in Polish poetry of the second half of the 20th century. Focusing on such leading names of modern and contemporary Polish poetry as Adam Zagajewski, Czesław Miłosz, Zbigniew Herbert, Wisława Szymborska, Tadeusz Różewicz, and Stanisław Barańczak, I aim to show how in their poetry the spatial side of return is generally less pronounced and consequential than the complex inner exploration that return may engender. In other instances, returns are more or less implicitly depicted as meaningless. By discussing poetic images of return over a rather long period, I also touch upon issues of cultural and literary development and change.